Improving Criteria and Feedback in Student Assessment in Law - Richard Johnstone; Jenny Patterson; Kim Rubenstein (Legal Education Review)
Spurred on by both the 1987 Pearce Report and the general changes to higher education spawned by the “Dawkins revolution” from 1988, there has been much critical self-evaluation leading to profound improvements to the quality of teaching in Australian law schools. Despite the changes there are still areas of general law teaching practice which have lagged behind recent developments in our understanding of what constitutes high quality teaching. One such area is assessment criteria and feedback. The project Improving Feedback in Student Assessment in Law is an attempt to remedy this. It aims to produce a manual containing key principles for the design of assessment and the provision of feedback, with practical yet flexible ideas and illustrations which law teachers may adopt or modify. Most of the examples have been developed by teachers at the University of Melbourne Law School. The project was supported in 1996 by a Committee for the Advancement of University Teaching grant and the manual will be published late in 1997. This note summarises the core principles which are elaborated further in the manual.